Strategi Implementasi Kesehatan Digital untuk Pencegahan Penyakit Kardiovaskular Jangka Panjang di Sektor Energi - Rezayyan, Jordi; Aulia, Syafira (Journal of Medical and Health Sciences, 2025)
Cardiovascular disease (CVD) is one of the leading causes of death in Indonesia and has a high prevalence among energy sector workers who are exposed to occupational stress, unhealthy lifestyles, and limited access to medical services. This study aims to analyze the implementation strategies of digital health for long-term CVD prevention in the energy sector. A descriptive-analytical method was used with a qualitative approach through semi-structured interviews involving occupational health managers, corporate medical personnel, and workers from three energy companies, supplemented by a review of national and international literature. Data were analyzed using thematic analysis techniques, focusing on enabling factors, barriers, and sustainability strategies. The findings indicate that successful implementation is influenced by company management support, the use of digital technologies such as mobile applications, telemedicine, and wearable devices, as well as active worker participation through education and health promotion programs. Key barriers include limited digital literacy, resistance to change, and infrastructure challenges. Nevertheless, digital health interventions have been shown to reduce CVD risk factors, raise worker awareness, and improve company productivity. This study concludes that digital health implementation strategies can serve as a long-term solution for CVD prevention in the energy sector. Ongoing collaboration between companies, medical personnel, and workers is essential to strengthen digital literacy, expand program coverage, and ensure the sustainability of digital health interventions as part of the company’s strategic investment.